KONSEP INTEGRATED MARKETING COMMUNICATION DALAM MENINGKATKAN BRAND IMAGE HOTEL GRAND SAHID JAYA JAKARTA - Hamzah, Radja Erland; Azhari, Reza Rahmat (JURNAL PUSTAKA KOMUNIKASI, 2019)
The purpose of this study was to find out what and how the Integrated Marketing Communication strategy was conducted by Grand Sahid Jaya Jakarta Hotel to improve Brand Image. This study uses the concept of Fours Step, a qualitative research method. The paradigm used in this study is the constructivist paradigm. This study uses three kinds of data collection techniques, namely primary data (in-depth interviews (depth interviews), observation) and secondary data. To test the validity of the data in this study, researchers used triangulation of source data to check the correctness of the data disclosed by the speakers. From the results of this study indicate that in improving the image of Grand Sahid Jaya Jakarta Hotel, the smart marketing program is one of the strategies carried out by Grand Sahid Jaya Jakarta Hotel in maintaining good relations with clients.